Evaluating Respiratory Distress Management among Nurses to Improve Evidence Base Practice: A Quantitative Study at Suntreso Hospital, Ghana - Buah, Thelma; Opoku, Albert; Asafo, T. A. Adjei; Arhinful, Frederick (British Journal of Healthcare and Medical Research, 2025)
Introduction: Respiratory distress is a prevalent and critical medical emergency that poses significant challenges for healthcare providers, particularly in emergency department settings. Respiratory distress is usually a medical emergency and is best managed by an interprofessional team that includes the emergency department physicians, nurses, and an intensivist. Objective: This study investigates the knowledge, practices, attitudes, and barriers to managing respiratory distress among healthcare professionals at Suntreso Government Hospital in Kumasi. Utilising the KAP (Knowledge, Attitude, Practices) model as the theoretical framework, the research aimed to identify gaps in the understanding and management of respiratory distress, which contributes substantially to morbidity and mortality rates. Methods: A descriptive cross-sectional study design with a quantitative approached was employed for the study. A structured questionnaire with a Cronbach’s Alpha value of 0.71 was used to collect data from 171 nurses, selected through a convenience sampling method. Statistical Package for Social Sciences (SPSS) was used for data analysis and descriptive statistics was presented with tables of percentages, bar chats and par charts. Results and Finding: The study findings showed that 54.8% of the studied nurses had an average level of knowledge, compared to 9.94% of them having good expertise. 54.97% exhibited moderate attitudes toward managing respiratory distress, and 87.71% of the nurses surveyed demonstrated poor practice. In comparison, less than one-third, 2.34%, showed a good practical level in managing respiratory distress. Conclusion: The study conclude the knowledge and practice gab in managing respiratory distress and therefore recommends regular and structured in-service training programs on respiratory distress management. These should be mandatory and conducted periodically, covering key areas such as emergency response protocols, oxygen therapy, and ventilatory support. Simulation-based learning and case scenario exercises should be incorporated to enhance practical competencies.